A graphic analysis method of electrochemical systems for low-grade heat harvesting from a perspective of thermodynamic cycles. (15th January 2020) - Chen, Ruihua; Deng, Shuai; Xu, Weicong; Zhao, Li
Abstract: Various electrochemical approaches for low-grade heat harvesting have been investigated in recent years. However, most current studies are based on electrochemistry methods, while thermodynamic methods that focus on the general energy conversion mechanism are relatively rare. In this study, to quantify the chemical energy of electrochemical systems, Gibbs free energy is introduced as the third dimension in the conventional T-S diagram from a perspective of thermodynamic cycles, and a graphic analysis method is proposed consequently. Then the ideal cycle, which could identify the conversion relationship among heat, work and chemical energy, is presented guided by the graphic analysis method. A discussion is presented as well to explain the non-ideality of actual cycles. Finally, as a representative case, the energy conversion mechanism and the efficiency expression of thermally regenerative electrochemical cycle are restated, to valid the graphic analysis method. The graphic analysis method polishes the thermodynamic theoretical system of electrochemical systems for heat harvesting where chemical energy matters, and leads to an in-depth understanding on the intrinsic energy conversion mechanism. Furthermore, the graphic analysis method would provide a theoretical guidance for integration of chemical energy into the construction of thermodynamic cycles, and even enlighten the boundary extension of thermodynamic cycles. Highlights: A novel graphic analysis method for ESHH is proposed. The ideal cycle of conversion among heat, work and chemical energy is presented. The efficiency expression of TREC considering irreversibility is restated.